Octreotide for Enterocutaneous Fistulas of Crohn's Disease. (1st September 2003) - Lavy, A; Yasin, K
Abstract : Crohn's disease is a chronic, life-long disease and has many troublesome complications. Fistulas are a part of Crohn's disease, and although there are many therapeutic modalities used in treating these fistulas they are only partially successful. As we are still very far from being able to cure it, the aim is to improve the patients' quality of life and to reduce the iatrogenic harm that may be caused by various treatment modalities. Somatostatin is an inhibitor of intestinal secretion and has been used to treat pancreatic and surgical fistulas. Therefore, we decided to treat enterocutaneous fistulas using somatostatin. METHODS: Five patients with Crohn's disease were treated with four daily injections of 300 µg octreotide. The total period of treatment was eight weeks. RESULTS: Closure of fistulas was achieved in four of the five patients. CONCLUSION: Somatostatin may have a role in treating Crohn's disease enterocutaneous fistulas and may prevent surgery or prolonged immunosuppressive therapy.